Intracystic magnetic resonance imaging in patients with autosomal dominant polycystic kidney disease: features of severe cyst infection in a case–control study. Issue 1 (December 2016) - Suwabe, Tatsuya; Ubara, Yoshifumi; Ueno, Toshiharu; Hayami, Noriko; Hoshino, Junichi; Imafuku, Aya; Kawada, Masahiro; Hiramatsu, Rikako; Hasegawa, Eiko; Sawa, Naoki; Saitoh, Satoshi; Okuda, Itsuko; et al.
Abstract Background The purpose of this study was to investigate the usefulness of intracystic MRI features for detection of severe cyst infection that is usually refractory to antibiotic therapy alone in patients with autosomal dominant polycystic kidney disease. Methods Seventy-six patients (88 episodes) with positive cyst cultures treated from January 2006 to December 2013 were enrolled as the cases for this case–control study, while 147 patients who continued to attend our hospital from January 2011 to December 2013 and did not have cyst infection diagnosed during that period were enrolled as the controls. Intracystic MRI findings were investigated. Results At least one of four intracystic MRI features (high signal intensity (SI) on diffusion-weighted images (DWI), fluid-fluid level, wall thickening, or gas) was found in all of the cases, but such findings were also detected in some controls. Intracystic gas was specific for cyst infection, but its sensitivity was only 1.1 %. A high intracystic SI on DWI showed a sensitivity of 86.4 %, but its specificity was lower at 33.3 %. Both the specificity and sensitivity of a fluid-fluid level or wall thickening were about 80 %. However, the specificity of these MRI features decreased as total liver and kidney volume (TLKV) increased, falling to 65.8 % in patients with organomegaly (TLKV > 8500 cm3 ). A cyst diameter > 5 cm was useful for detecting severely infected cysts that needed drainage, and specificity was increased by combining the other four MRI findings with a cyst diameter > 5 cm. Conclusions MRI with DWI was useful for detecting severe cyst infection in ADPKD. While the specificity of MRI alone was not high enough in patients with organomegaly, combining the four MRI features with abdominal pain, sequential MRI changes, or cyst diameter > 5 cm improved detection of severely infected cysts in these patients.